Colistin Selection of the Mcr-1 Gene in Broiler Chicken Intestinal Microbiota - Pedro Miguela-Villoldo; Miguel A. Moreno; Agustín Rebollada-Merino; Antonio Rodríguez-Bertos; Marta Hernández; David Rodríguez-Lázaro; Alejandro Gallardo; Alberto Quesada; Joaquín Goyache; Lucas Domínguez; María Ugarte-Ruiz (MDPI AG, 2021)
Colistin has a long story of safe use in animals for the treatment and prevention of certain bacterial diseases. Nevertheless, the first description of the mcr-1 gene showed that colistin resistance can spread by horizontal gene transfer and changed the landscape. This study aimed to assess the effect of colistin administration on the dispersion of resistance in the microbiota of day-old broiler chicks and how the presence of mcr-1 genes influences the spread of colistin resistance determinants. In this study, 100 one-day-old chicks were divided into four groups of 25 animals (G1, G2, G3, and G4). Animals from G3/G4 were challenged with mcr-1-carrying Salmonella (day 7), while colistin (600 mg/L) was administered daily to G2/G4 animals through drinking water (from day 8 to day 15). Two quantitative PCR assays were performed to compare the amount of Salmonella and mcr-1 that were present in the caecal samples. We observed that levels of mcr-1 were higher in G3/G4 animals, especially G4, due to the spread of mcr-1-carrying Salmonella. On day 21, Salmonella levels decreased in G4, reaching similar values as those for G3, but mcr-1 levels remained significantly higher, suggesting that colistin may accelerate the spreading process when mcr-1-carrying bacteria reach the gut.